2018
DOI: 10.1007/s00424-018-2246-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects of the phosphate transporters NaPi-IIa and NaPi-IIb: mutations and disease associations

Abstract: The Na-dependent phosphate transporter NaPi-IIa (SLC34A1) is mostly expressed in kidney, whereas NaPi-IIb (SLC34A2) has a wider tissue distribution with prominent expression in the lung and small intestine. NaPi-IIa is involved in renal reabsorption of inorganic phosphate (Pi) from urine, and patients with biallelic inactivating mutations in SLC34A1 develop hypophosphatemia, hypercalcemia, hypercalciuria and nephrocalcinosis, and nephrolithiasis in early childhood. Monoallelic mutations are frequent in the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 106 publications
0
17
0
Order By: Relevance
“…Humans with NHERF1 inactivating mutations exhibit elevated phosphate excretion and a prominent bone phenotype with fractures (13,14). Likewise, knockout of Npt2a 5 (15) or SLC34A1 mutations disrupt phosphate metabolism with a constellation of mineral-ion and skeletal disorders (16,17).…”
mentioning
confidence: 99%
“…Humans with NHERF1 inactivating mutations exhibit elevated phosphate excretion and a prominent bone phenotype with fractures (13,14). Likewise, knockout of Npt2a 5 (15) or SLC34A1 mutations disrupt phosphate metabolism with a constellation of mineral-ion and skeletal disorders (16,17).…”
mentioning
confidence: 99%
“…Within the proximal tubule, phosphate transport from the ultrafiltrate across the proximal tubule epithelium is an energy dependent process that requires sodium [38]. The three renal sodium phosphate cotransporters, NaPi2a, NaPi2c, and PiT2, are all localised on the apical brush border membrane of renal proximal tubule cells and use the energy derived from the transport of sodium down its gradient to move inorganic phosphate from the luminal filtrate into the cell [39]. Mouse knockout experiments have shown that NaPi2a accounts for up to 70% of phosphate transport [40].…”
Section: Phosphate Handling In the Kidney In Healthy Individualsmentioning
confidence: 99%
“…Collectively, preclinical studies have demonstrated that high phosphate diet appears to be linked to low expression of NaPi2b in the intestine, whereas dietary phosphate restriction leads to strong upregulation of NaPi2b [39,[80][81][82][83]. Moreover, many patients with advanced stages of CKD develop metabolic acidosis which in turn stimulates the expression and activity of NaPi2b [84].…”
Section: Dietary Phosphate Restrictionmentioning
confidence: 99%
“…Mutations in SLC34A1 are also causal for AR infantile hypercalcemia [58][59][60], with many cases reported in the literature. Conversely, it was proposed by some [35,[61][62][63] and contested by others [64][65][66] that monoallelic mutations in the same gene determine AD hypophosphatemia and nephrocalcinosis, particularly in association with environmental factors. A dominant negative effect of heterozygous NaPiIIa mutations could not be demonstrated and phosphate transport has been mildly affected in some of the experiments [64,66].…”
Section: Genetic and Phenotypic Heterogeneity Complicate Genetic Analmentioning
confidence: 99%